2020
DOI: 10.7196/samj.2020.v110i2.13684
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diagnostic methods on the diagnosis of Clostridiodes difficile infection

Abstract: Clostridiodes difficile is a common cause of healthcare-associated diarrhoea. The clinical outcome depends on host factors and the virulence of the toxin-producing strain. This organism causes disease that ranges in severity from asymptomatic colonisation to severe diarrhoea, pseudomembranous colitis, toxic megacolon, colonic perforation and death. [1-3] The principal risk factor for C. difficile infection (CDI) is prior antibiotic therapy. [4] Results of a systematic review assessing the epidemiology of CDI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In a study conducted 2014–2017 in South Africa demonstrated the impact of diagnostic methods on the diagnosis of C. difficile infection, Nomlomo et al found a 15.9% positivity rate when using an algorithm approach (consisting of EIA followed by PCR) versus 11.4% and 21.1% when using a toxin EIA and PCR. 27 However, neither of the two accepted references tests was performed as the comparator test in this study. We showed a 16.6% TC positivity rate which is very similar to Nomlomo et al’s finding using the algorithm approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted 2014–2017 in South Africa demonstrated the impact of diagnostic methods on the diagnosis of C. difficile infection, Nomlomo et al found a 15.9% positivity rate when using an algorithm approach (consisting of EIA followed by PCR) versus 11.4% and 21.1% when using a toxin EIA and PCR. 27 However, neither of the two accepted references tests was performed as the comparator test in this study. We showed a 16.6% TC positivity rate which is very similar to Nomlomo et al’s finding using the algorithm approach.…”
Section: Discussionmentioning
confidence: 99%
“…We showed a 16.6% TC positivity rate which is very similar to Nomlomo et al’s finding using the algorithm approach. 27 …”
Section: Discussionmentioning
confidence: 99%
“…C. difficile , a Gram-positive bacteria, is suggested to cause pseudomembranous colitis, swelling or inflammation of the colon ( Nomlomo and Nana, 2020 ). A retrospective study of the Nationwide Readmissions Database in the United States suggested that diabetes mellitus correlates to 30-day all-cause readmissions for C. difficile –induced enterocolitis ( Kichloo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%